Effects of the Modified DASH Diet on Adults With Elevated Blood Pressure or Hypertension: A Systematic Review and Meta-Analysis - Guo, Ru; Li, Nian; Yang, Rong; Liao, Xiao-Yang; Zhang, Yu; Zhu, Ben-Fu; Zhao, Qian; Chen, Lingmin; Zhang, Yong-Gang; Lei, Yi (Frontiers in Nutrition, 2021)
Background: The modified Dietary Approaches to Stop Hypertension (DASH) diet was a potentially effective treatment for pre-hypertensive and hypertensive patients. The evidence for the effect of the modified DASH diet on blood pressure reduction was inconsistent. The study was designed to assess the effects of the modified DASH diet on blood pressure (BP) in hypertensive and pre-hypertensive adults. Methods: We searched Medline, Embase, CENTRAL, CNKI, VIP, Wanfang Data, SINOMED, Google Scholar, the World Health Organization’s International Clinical Trials Registry Platform, and Clinicaltrials.gov from inception to October 1st, 2020. Randomized controlled trials (RCTs) assessing the effects of the modified DASH diet on systolic and diastolic BP, cardiovascular risk factors (body weight, body mass index, waist circumference, fasting glucose, blood lipids), cardiovascular events, and all-cause mortality were included. Statistical analysis was performed using Revman 5.3 software. Results: A total of 10 RCTs were included. Compared with control diet, the modified DASH diet could reduce mean systolic (−3.26 mmHg; 95% confidence interval −5.58, −0.94 mmHg; P = 0.006) and diastolic (−2.07 mmHg; 95% confidence interval −3.68, −0.46 mmHg; P = 0.01) BP. Compared with the controlling diet, the modified DASH diet could reduce systolic BP to a greater extent in trials with a mean baseline BP ≥140/90 mmHg compared with <140/90 mmHg. Diastolic BP reduction was greater when the mean body mass index was ≥30 kg/m2 than <30 kg/m2. Diastolic BP reduction was more marked in trials with a follow-up time of >8 weeks compared with ≤8 weeks. The modified DASH diet could affect mean waist circumference (difference: 1.57 cm; 95% confidence interval −2.98, −0.15) and triglyceride concentration (difference: 1.04 mol/L; 95% confidence interval −1.47, −0.60). Conclusions: The modified DASH diet can reduce BP, waist circumference, and triglyceride concentration in hypertension patients. A higher baseline BP is associated with more marked systolic and diastolic BP reduction. Systematic review registration: PROSPERO registration number: CRD42020190860